PENERAPAN METODE DISCOVERY DENGAN MEDIA KARTU BERGAMBAR DALAM PENINGKATAN KERJASAMA DAN HASIL BELAJAR IPS TENTANG AKTIVITAS EKONOMI KELAS IV SD NEGERI 1 BUMIREJO TAHUN 2015/2016 OLEH: SHONIF MUZAYYIN1, TRI SAPTUTI SUSIANI2, SALIMI3 PGSD FKIP UNS SURAKA - Muzayyin, Shonif (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Discovery Methods with Flashcard Media in Improving Students' Cooperation and Learning Outcomes of Social Science Learning about Economic Activity at the Fourth Grade Students of SD Negeri Bumirejo 1 in Academic Year of 2015/2016. This research is motivated by the lack of students' cooperation in discussion activity, and low students' learning outcomes, especially in social science learning. The purpose of this research is to improve students' collaboration and students' learning outcomes of the fourth grade students in SDN Bumirejo through classroom action research related to the material of economic activity. This research is a collaborative research conducted in three cycles, and each cycle consisted of planning, action, observation, and reflection. The result of this research is the application of discovery methods with flashcard media can improve students' collaboration when discussion and students' learning outcomes. It can be seen from the results of research showing that the percentage of students who meet the target achievements of cooperation is 34.3% at first cylce, 74.2% at second cycle and 88% at third cycle. As for the results of students' learning outcomes, the percentage of students' completeness is 65.71% at first cycle, 62.86% at second cycle and 90.91% at third cycle.Keywords: discovery method, flashcard media, collaboration, learning outcomes Abstrak: Penerapan Metode Discovery dengan Media Kartu Bergambar dalam Peningkatan Kerjasama dan Hasil Belajar IPS tentang Aktivitas Ekonomi Kelas IV SDN 1 Bumirejo Tahun 2015/2016. Penelitian ini dilatar belakangi oleh rendahnya kerjasama siswa ketika berdiskusi, dan belum maksimalnya hasil belajar siswa khususnya pada mata pelajaran IPS. Tujuan penelitian ini yaitu untuk meningkatkan kerjasama siswa dan hasil belajar siswa kelas IV SDN Bumirejo, pada tindakan kelas yang berkaitan dengan materi aktivitas ekonomi. Penelitian ini merupakan penelitian kolaboratif yang dilaksanakan selama tiga siklus, dan setiap siklusnya melewati tahap perencanaan, pelaksanaan, observasi, serta refleksi. Hasil setelah penelitian yaitu penerapan metode discovery dengan media kartu bergambar dapat meningkatkan kerjasama siswa ketika diskusi dan juga hasil belajar siswa. Hal ini dapat dilihat dari hasil penelitian yang menunjukan bahwa pada siklus I persentase siswa yang memenuhi capaian target kerjasama yaitu 34,3%, siklus II 74,2%, dan siklus III 88%. Sedangkan untuk hasil belajarnya, pada siklus I persentase ketuntasan siswa yaitu 65,71%, siklus II 62,86% dan siklus III 90,91%.Kata Kunci: Metode discovery, Media kartu bergambar, kerjasama, hasil belajar.